State Responsibility and Liability in Climate Change Mitigation in Section International Law Analysis - Mohammed, Said Salih; Jasim, Imad Obaid; Al-Bayati, Adnan Khalil Kazem; Kabrch, Jassim Kadhi; Khlaponin, Dmytro (Journal of Ecohumanism, 2024)
Background: In light of the significant impacts of climate change, there is a growing recognition of the need for international legal mechanisms to hold states accountable for their actions leading to environmental degradation. The concept of state responsibility, a well-established tenet in the field of international law, provides a framework through which the actions and obligations of states may be assessed concerning the issue of climate change. Objective: The primary aim of this study is to examine the complexities surrounding State duty and liability in the context of climate change mitigation, with a specific focus on the international legal aspects. Methods: A comprehensive examination of global agreements, procedures, and significant judicial decisions was conducted. The implications of political activities on global climate change were examined by analyzing statistical data provided by the Intergovernmental Panel on Climate Change (IPCC) and the World Meteorological Organization (WMO). Results: The study's findings highlight that a significant proportion of worldwide greenhouse gas emissions, over 60%, may be linked to the industrial activity of a select group of 10 nations. Moreover, despite the widespread ratification of international legal instruments such as the Paris Agreement, there needs to be more real legal measures taken against significant emitters. Fewer than 10% of these emitters have faced international legal consequences for non-compliance. Conclusion: The enforcement of concepts regarding State duty and liability concerning climate change mitigation needs to be more robust within international law. There is a pressing need to strengthen the international legal system to establish responsibility for states at fault, thereby promoting the development of a more sustainable global environment.